Motorway widening seminar Thursday 30 June 1994 at The National Motorcycle Museum, West Midlands organized by the Institution of Civil Engineers in conjunction with the Highways Agency, the Institution of Highways and Transportation, Federation of Civil Engineering Contractors. (Institution of Civil Engineers, 1994)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a seminar held at the National Motorcycle Museum, West Midlands, on 30 June 1994.